Functional Analysis of the env Open Reading Frame in Human Endogenous Retrovirus IDDMK(1,2)22 Encoding Superantigen Activity - Lapatschek, Matthias (American Society for Microbiology, 2000)
Mice harbor a family of endogenous retroviruses, the mouse mammary tumor viruses (MMTV), which encode superantigens. These superantigens are responsible for the deletion of T cells expressing certain Vβ chains of the T-cell receptor in the thymus. Human T cells are able to recognize MMTV-encoded superantigens presented by human major histocompatibility complex class II-positive cells. Owing to this and to the similarity of the human and murine immune systems, it was speculated that human endogenous retroviruses might also code for superantigens. Recently, it was reported that a proviral clone (IDDMK(1,2)22) of the human endogenous retrovirus family HTDV/HERV-K encodes a superantigen. The putative superantigen gene was located within the env region of the virus. Stimulated by these findings, we amplified by PCR and cloned into eucaryotic expression vectors open reading frames (ORFs) which were identical or very similar to IDDMK(1,2)22. When we transfected these vectors into A20 cells, a murine B-cell lymphoma, we were able to demonstrate mRNA expression and protein production. However, we did not find any evidence that the ORF stimulated human or murine T cells in a Vβ-specific fashion, the most prominent feature of superantigens.